Rapid determination of bacterial aminoglycoside resistance in environmental samples using membrane electrospray ionization mass spectrometry. (August 2016) - Fan, Liusheng; Ke, Ming; Yuan, Min; Pu, Ji; Li, Juan; Lu, Jinxing; Xu, Jianguo; Zhang, Mei; Xu, Wei
Abstract : Rationale: Antibiotic resistance in pathogenic bacteria is becoming a global public health problem, such as aminoglycoside resistance encoded by the armA gene. Although many methods have been reported, rapid analysis of environmental samples is still challenging. Method: A rapid analytical method was developed in this study to determine bacterial aminoglycoside resistance using membrane electrospray ionization mass spectrometry (MESI‐MS). Precursor/product‐ion pairs of ArmA unique peptides were detected with minimal sample preparation. Standard peptides were synthesized and used for developing and validating the methodology, and then the method was verified by both ArmA positive and ArmA negative simulated environmental samples. Results: A rapid method for determination of bacterial aminoglycoside resistance was developed using MESI‐MS/MS. The bacterial cultural time was optimized to 2 hours, and the precision, accuracy and recovery of this method were investigated. The peptide IHSSTNER (IR‐8) unique to ArmA in simulated environmental samples can be successfully identified within 3 hours. Conclusions: The novel assay offered a rapid method to determine bacterial aminoglycoside resistance with high sensitivity, accuracy and precision in simulated environmental samples. This method could also be applied to identify other drug‐resistance proteins in clinical/environmental samples. Copyright © 2016 John Wiley & Sons, Ltd.